2017
DOI: 10.21014/acta_imeko.v6i3.461
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Research of Iron Casting Technologies in the Town of Juketau during the Golden Horde Period

Abstract: The work features the results of interdisciplinary research of cast iron dishware fragments discovered in the territory of one of the largest towns of the Volga-Kama region in the Golden Horde period. The microstructure of cast iron samples and surface mapping have been studied using scanning electron microscopy  (SEM), and the microelemental composition was determined by emission spectral analysis (ESA). The characteristic features of the manufacturing technology have been revealed as a result of research of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The first group is composed of small pores present in all the studied fragments from the Selitrennoye settlement and the BS-65 sample from the Bolgar settlement. Recently, comparative microscopy and chemical studies of cast iron products [3,4,61] suggested that a historical school of cast iron craft in Bolgar was quite advanced in comparison with the Selitrennoye settlement. It is believed that cast iron products from the Bolgar settlement are of higher quality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first group is composed of small pores present in all the studied fragments from the Selitrennoye settlement and the BS-65 sample from the Bolgar settlement. Recently, comparative microscopy and chemical studies of cast iron products [3,4,61] suggested that a historical school of cast iron craft in Bolgar was quite advanced in comparison with the Selitrennoye settlement. It is believed that cast iron products from the Bolgar settlement are of higher quality.…”
Section: Resultsmentioning
confidence: 99%
“…If small pores are characterized by the so-called "belt" texture or Observed small pores may occur during the casting of medieval products, and their formation can be associated with two processes when cooling a cast iron product. There is a formation of various phases in the Fe-C system [3,4,61,62], including graphite from excess carbon content, and the uneven cooling of the cast of cauldrons. It is known that molds made of a densified sand-clay mixture were used for casting cauldrons [3,4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations